Forestry for farmers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
A forestry advisor for the Co-operative League of the United States describes a programme to build co-operation between the forestry services and local communities in eastern Zambia. The programme has involved stakeholder workshops to write management plans, and support for more productive agriculture.